The Differential Effects of Age on the Association Between Childhood Socioeconomic Disadvantage and Subjective Symptoms of Dementia Among Older Japanese People - Murayama, Hiroshi (J Epidemiol, 2019)
BACKGROUND: Despite increasing evidence of an association between childhood socioeconomic disadvantage and cognitive outcomes, such as dementia and cognitive decline, in Western countries, there are no studies on this association from non-Western societies. We investigated the relationship between childhood socioeconomic status (SES) and subjective symptoms of dementia among community-dwelling older Japanese people and examined age and sex variations in this association. METHODS: Data were derived from a cross-sectional survey for all community-dwelling individuals aged 65 years and over in Adachi, Tokyo (n = 132,005). We assessed subjective dementia symptoms using a self-administered dementia checklist, which was validated by comparison with the Clinical Dementia Rating scale. RESULTS: Data from 75,358 questionnaires were analyzed. After adjusting for potential covariates, lower childhood SES was associated with greater likelihood of subjective dementia symptoms. We found a significant interaction between childhood SES and age on subjective dementia symptoms but no interaction between childhood SES and sex. Age-stratified analysis indicated that the association between lower childhood SES and subjective dementia symptoms was stronger in the ≥75 years subgroup than in the 65–74 years subgroup, indicating an effect modification of age on this association. CONCLUSIONS: Our findings suggested that low SES in childhood might have a long-term influence on dementia symptoms in late life and that this influence varied by age. This differential association might be explained by the social and historical context in Japan (ie, World War II, postwar chaos, and high economic growth) that has shaped participants’ early experiences.